Comment on "Next‐Generation Ice Core Technology Reveals True Minimum Natural Levels of Lead (Pb) in the Atmosphere: Insights From the Black Death" by More et al. Issue 5 (31st May 2018) - Bindler, Richard
Abstract: Over the past four decades numerous studies of lake sediment, marine sediment, and peat from sites in close proximity to mining or metallurgical centers and in remote locations have detailed local and regional histories of lead (Pb) pollution in Europe. Contrary to More et al.'s (2017, https://doi.org/10.1002/2017GH000064 ) claim that "previous assumptions about preindustrial "natural" background lead levels in the atmosphere have been misleading, " these studies have clearly shown that true natural background conditions occurred more than 2, 500 or even 3, 500 years ago, and Pb pollution has proceeded uninterrupted since. The implications of this have been discussed within the context of environmental policy, for example, European Water Framework Directive. Though these records reflect a common European narrative of mining, metallurgy, and pollution, each reflects a combination of local and regional events, leading to differences in the timing and intensity of changes in each Pb record. No one record—ice or otherwise—fully represents the three millennia Pb pollution history in Europe. While the resolution of the ice record is impressive, there are questions about its interpretation. First, the authors discount local and regional Pb sources, whereas there is a close connection between the mining history in an area 40 km from the glacier and changes in a nearby lake Pb record; second, significant changes in ice chemistry cooccurring with the lowest Pb values are overlooked. A sharp increase in Ca/Fe ratios occurs precisely with the steepest Pb declines during the Black Death and mid‐1400s, suggesting additional processes influencing the Pb record. Key Points: Four decades of research have detailed the Pb pollution history in Europe, including background levels occurring >3, 000 years ago Mining and metallurgy occurred in a wide range of locations resulting in local and regional histories within a common European narrative Colle Gnifetti record contains many interesting details, but further examination of the chemistry is needed to understand the Pb record